Imaging analysis of fines migration during water flow with salinity alteration. (November 2018) - Yu, M.; Hussain, F.; Arns, J.-Y.; Bedrikovetsky, P.; Genolet, L.; Behr, A.; Kowollik, P.; Arns, C.H.
Highlights: High- and low-salinity brine was injected into a Berea sandstone core plug. Micro-CT images of the core plug was taken before and after injection. SEM-EDS analysis showed clay fines production. Laboratory measurements showed an 80% decrease in permeability. Image analysis show clay straining near the production end of the core plug. Abstract: Fines migration is considered one of the mechanisms of permeability alteration associated with water injection in aquifers and oil reservoirs. However, there has been limited direct evidence of fines migration. This paper presents conclusive evidence for the migration and capture of fines, obtained from experiments utilising 3D micro-CT imaging. A single-phase flooding experiment was performed on a Berea sandstone core plug. First, a micro-CT image of the dry core plug was taken before flooding. Then the core plug was saturated with 4% NaCl brine, further injected with 4% NaCl brine, and finally flushed with fresh water. The pressure difference across the core plug was monitored during these fluid injections, and produced water samples were analysed for fines concentration and type by combining particle counting methods and Scanning Electron Microscope – Energy Dispersive Spectroscopy (SEM-EDS) analysis. After the flooding experiment, the core plug was reimaged, and the second micro-CT image was compared to the first to quantify the fines migration. Laboratory measurements showed an 80% decrease in permeability during fresh water injection, which was accompanied by a large concentration of fines in the produced-water samples. SEM-EDS analysis of those fines showed them to be clay. Comparison of initial and final tomogram images showed increased micro-CT intensity in the flow direction near the core outlet, due to relocation of clay. Permeability computations made on micro-CT images showed a 50% decrease in permeability during fresh water injection, due to fines straining near the core outlet. Modelling of retention concentration along the core length and of breakthrough fines concentration versus pore volume injected indicated that fines retention was nonlinear.